Salt-marsh evolution at Northwick and Aust warths, Severn Estuary, UK: a case of constrained autocyclicity. - Haslett, Simon K.; Allen, John R.L. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2014)
Historic maps, remote imagery and field surveys reveal that a terraced sequence of four salt marshes has arisen on a decadal-centennial time-scale over a frontage of about 4 km at Northwick and Aust warths exposed to westerly to northerly winds on the east bank of the Severn Estuary, UK. Except for the youngest marsh, at present very immature, each marsh built up through differential sedimentation from a mudflat until the outer zone reached a critical steepness; at that point wave-attack caused erosion that led to the rapid landward retreat of a bold, laterally extensive, marsh-edge cliff. This observed behaviour is consistent with previous models of autocyclic marshes, but evidence suggests that the extrinsic factor of medium-scale changes in wind-wave climate constrained the particular timing of marsh responses.